Activation of Human NK Cells by Bordetella pertussis Requires Inflammasome Activation in Macrophages - Kroes, Michiel M.; Mariman, Rob; Hijdra, Daniëlle; Hamstra, Hendrik-Jan; van Boxtel, Karlijn J. W. M.; van Putten, Jos P. M.; de Wit, Jelle; Pinelli, Elena (Frontiers in Immunology, 2019)
Pertussis is a highly contagious respiratory infection caused by the bacterium Bordetella pertussis. Humans are the only known natural reservoir of B. pertussis. In mice, macrophages and NK cells have a key role in confining B. pertussis to the respiratory tract. However, the mechanisms underlying this process, particularly during human infections, remain unclear. Here we characterized the activation of human macrophages and NK cells in response to B. pertussis and unraveled the role of inflammasomes in this process. NLRP3 inflammasome activation by B. pertussis in human macrophage-like THP-1 cells and primary monocyte-derived macrophages (mo-MΦ) was shown by the visualization of ASC-speck formation, pyroptosis, and the secretion of caspase-mediated IL-1β and IL-18. In contrast to macrophages, stimulation of human CD56+CD3- NK cells by B. pertussis alone did not result in activation of these cells. However, co-culture of B. pertussis-stimulated mo-MΦ and autologous NK cells resulted in high amounts of IFNγ secretion and an increased frequency of IL-2Rα+ and HLA-DR+ NK cells, indicating NK cell activation. This activation was significantly reduced upon inhibition of inflammasome activity or blocking of IL-18 in the mo-MΦ/NK cell co-culture. Furthermore, we observed increased secretion of proinflammatory cytokines in the B. pertussis-stimulated mo-MΦ/NK co-culture compared to the mo-MΦ single culture. Our results demonstrate that B. pertussis induces inflammasome activation in human macrophages and that the IL-18 produced by these cells is required for the activation of human NK cells, which in turn enhances the pro-inflammatory response to this pathogen. Our data provides a better understanding of the underlying mechanisms involved in the induction of innate immune responses against B. pertussis. These findings contribute to the knowledge required for the development of improved intervention strategies to control this highly contagious disease.